Nanowire based bioprobes for electrical monitoring of electrogenic cells. (29th October 2018) - Casanova, A; Bettamin, L; Blatche, M-C; Mathieu, F; Martin, H; Gonzalez-Dunia, D; Nicu, L; Larrieu, G
Abstract: The continuous miniaturization of electronic components and the emergence of nano-biotechnology has opened new perspectives to monitor electrical activities at the single cell level. Here, we describe the creation of very high surface-to-volume ratio passive devices (vertical nanowire probes) using large-scale fabrication process, allowing to follow the electrical activity of mammalian neurons. Based on conventional silicon processing, the silicon nanowires were silicided in platinum in order to improve their electrochemical performances and to guarantee their biocompatibility. Very high signal to noise ratio was achieved (up to 2000) when measuring spontaneous action potentials. Moreover, this bio-platform was used to record the impact of various bio-chemical and electrical stimulations on neuronal activity. To conclude, this study proposes a thorough comparison of the characteristics and performances of these new nanowire-based nanoprobes with the main alternative systems published up to now.